MULTIMODAL UKRAINIAN BRAND NARRATIVE: SEMIOTICS, STRUCTURE, ARCHETYPES - Nataliia K. Kravchenko; Liudmyla O. Shanaieva-Tsymbal (Вісник університету ім. А. Нобеля. Серія Філологічні науки)
The aim of the study is to identify the structural-narrative, semiot﻿ic, and archetypal properties of the Ukrainian multimodal narrative as a semiotic space of secondary signification and social mythologization. The data for analysis include slogans and promotional multimodal videos (video narratives) of the Ukrainian brand “Золотий вік” (Golden Age). Based on multimodal research, semiotics and advertising mythology theories, as well as the theories of cultural archetypes, and utilizing multimodal, narrative, narrative-semiotic, and archetypal analysis, in conjunction with conceptual integration tools, the article has achieved the following key results. The Ukrainian brand narrative is a multimodal discursive construct formed by a combination of multiple semiotic codes realized through verbal and non-verbal sign systems via auditory and visual channels. The modules are integrated through multimodal video narratives, constructing a semiotic world integrated with the secondary signified “love” and the associated concepts that replace the denotative meaning of the brand as a jewelry company and its products as ornaments. The secondary signified is verbalized through slogans, visualized through plots, voiced by background songs or voice-over narrators, and encoded by cultural codes in their intertextual and archetypal aspects. Multimodal video-narratives, featuring various characters, narrative plots, and formal-narrative structures, exhibit isomorphism with respect to the possible worlds they construct, archetypal images, motifs, and characters, as well as analogous narrative plots with differing levels of reduction in structural narrative elements. The verbal module, based on a slogan, as well as invariant auditory accompaniment common to all video narratives – the song “Love” and off-screen narrative, supports a hermeneutic code because it contains a key metaphor based on the slogan and peripheral metaphorical components that reveal the conceptual features of its target space. The audio-visual module forms a proaritic code based on the narrative plots of advertising clips in a three-component possible world: extratextual frame narrative, textual pseudoreal narrative, and fairytale narrative. The cultural code is realized through various multimodal resources. The slogan and the brand name include explicit references to the source intertext based on the song. In the video narratives, techniques of interdiscursivity are used, combining elements of melodrama, a romantic story, and a fairy tale, as well as references to archetypal images, motifs, and elements of the archetypal cyclical time. Central to these are the archetypal images of dreams, magic, hearts, and motifs of the magical helper-giver, the journey, crossroads, and magical transformation of those who receive a branded gift. The main archetypes are those of gold and the ring-circle, associated with the symbolism of the sun. Cyclical temporality, associated with mythological time, is actualized by recurring motifs and underpins the unity of love and preciousness from the perspective of the connotations of “eternity” – as eternal spiritual and material values. The semantic code of connotations is related to the secondary signification meanings, which associate the brand’s products with “embodied” love and is based on all the brand’s narrative modules, constructing its social mythology. The symbolic code is based on archetypal symbols and the core value of the brand in its implicit opposition to values foreign to the brand, appealing to the motivational value of “love and the need for belonging” in the hierarchy of human motivations. The perspective for further research is the analysis of the pragmatics of multimodal narratives in Ukrainian brands.